2016
DOI: 10.1016/j.drugpo.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

“Not human, dead already”: Perceptions and experiences of drug-related stigma among opioid-using young adults from the former Soviet Union living in the U.S.

Abstract: Background Young people from the former Soviet Union (FSU) in the U.S. are engaging in opioid and injection drug use (IDU) in substantial numbers, paralleling nationwide trends. Yet opioid-using FSU immigrants face distinctive acculturation challenges, including perceived stigmatisation as drug users within their immigrant communities, which may exacerbate the negative health and psychosocial consequences of such use. Methods This qualitative study draws on semi-structured interviews with 26 FSU immigrant yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 63 publications
(81 reference statements)
0
42
0
2
Order By: Relevance
“… 45 More specifically, participants across various studies reported compounded effects on treatment decisions of being both substance users and older, 57 , 67 a member of a racial or ethnic minority, 8 , 50 , 59 , 64 , 68 , 69 HIV-positive, 61 dually diagnosed with depression, 11 or female. 6 , 30 , 37 , 50 , 54 , 56 , 64 , 70 74 Females in several studies had a number of additional stigmas, including that of being pregnant, 54 incarcerated, 72 or black. 74 Stigmas were particularly influential on women when their substance use and/or usage of treatment services had implications for child-custody arrangements.…”
Section: Resultsmentioning
confidence: 99%
“… 45 More specifically, participants across various studies reported compounded effects on treatment decisions of being both substance users and older, 57 , 67 a member of a racial or ethnic minority, 8 , 50 , 59 , 64 , 68 , 69 HIV-positive, 61 dually diagnosed with depression, 11 or female. 6 , 30 , 37 , 50 , 54 , 56 , 64 , 70 74 Females in several studies had a number of additional stigmas, including that of being pregnant, 54 incarcerated, 72 or black. 74 Stigmas were particularly influential on women when their substance use and/or usage of treatment services had implications for child-custody arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, targeted outreach efforts to engage the new generation of young opioid users (including those who inject, as well as those who have not transitioned to regular in-jection) should be developed to involve them in harm reduction pro-grams, inform them of the HCV/HIV and other risks associated with drug injection, provide OD prevention/response training with na-loxone, and reduce stigma associated with services such as syringe exchange and methadone maintenance which can be high in this group (Frank et al, 2015; Gunn & Guarino, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The finding that participants' first overdose tended to occur < 6 months after their first episode of drug treatment suggests that treat-ment programs have a critical role to play in expanding access to overdose prevention/reversal education and naloxone (especially since the period immediately after leaving drug treatment is a well-known time of heightened risk for overdose). Finally, targeted outreach efforts to engage the new generation of young opioid users (including those who inject, as well as those who have not transitioned to regular in-jection) should be developed to involve them in harm reduction pro-grams, inform them of the HCV/HIV and other risks associated with drug injection, provide OD prevention/response training with na-loxone, and reduce stigma associated with services such as syringe exchange and methadone maintenance which can be high in this group (Frank et al, 2015; Gunn & Guarino, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Quanto às pessoas dependentes de drogas, verificou-se que muitos demonstram medo de expor fatos sobre a própria condição devido ao estigma, desconfiança e à hipervigilância, como por exemplo, nas tentativas de suicídio. Já os familiares omitem a dependência para que não sejam rejeitados, alvo de inferiorização ou responsabilizados pela dependência de seus ente querido (11,(15)(16) .…”
Section: Discussionunclassified
“…Tais questões culminam no estado pleno das desigualdades, denominado exclusão social. Caracterizado pelo processo acumulativo e multidimensional que separa e inferioriza as pessoas, os grupos, as comunidades e os territórios (4,12,15) . A exclusão social coexiste em vários tipos de fenômenos sociais, tais como o desemprego, a marginalidade, o preconceito e o pauperismo (17)(18) .…”
Section: Discussionunclassified